Microporous activated carbons from lignocellulosic biomass by KOH activation. Issue 12 (29th July 2020) - Bag, Oznur; Tekin, Kubilay; Karagoz, Selhan
Abstract: Oak wood samples were converted into activated carbons via chemical activation with KOH. The effects of KOH concentration and temperature on the yields and characteristics of the activated carbons were investigated; the yield of the activated carbons decreased with increased temperature and impregnation ratio. The lowest yield of activated carbon was obtained at the highest temperature (800 °C), with the highest KOH concentration of 100 wt%. The BET surface area of the activated carbons was comparable to that of commercially-activated carbon. The highest BET surface area of the activated carbon was 1662 m 2 .g −1, obtained at 800 °C with 50 wt% KOH concentration. KOH activation resulted in microporosity development in activated carbons.